Fuzzy clustering of intuitionistic fuzzy data. (28th April 2008) - Pelekis, Nikos; Iakovidis, Dimitris K.; Kotsifakos, Evangelos E.; Kopanakis, Ioannis
Challenged by real-world clustering problems this paper proposes a novel fuzzy clustering scheme of datasets produced in the context of intuitionistic fuzzy set theory. More specifically, we introduce a variant of the Fuzzy C-Means (FCM) clustering algorithm that copes with uncertainty and a similarity measure between intuitionistic fuzzy sets, which is appropriately integrated in the clustering algorithm. We describe an intuitionistic fuzzification of colour digital images upon which we applied the proposed scheme. The experimental evaluation of the proposed scheme shows that it can be more efficient and more effective than the well-established FCM algorithm, opening perspectives for various applications.